Clinical routine acquisition protocol for 3D relaxation-compensated APT and rNOE CEST-MRI of the human brain at 3T - Goerke, Steffen; Breitling, Johannes; Korzowski, Andreas; Paech, Daniel; Zaiß, Moritz; Schlemmer, Heinz-Peter; Ladd, Mark E.; Bachert, Peter (Magnetic Resonance in Medicine, 2021)
Purpose The value of relaxation-compensated amide proton transfer (APT) and relayed nuclear Overhauser effect (rNOE) chemical exchange saturation transfer (CEST)-MRI has already been demonstrated in various neuro-oncological clinical applications. Recently, we translated the approach from 7T to a clinically relevant magnetic field strength of 3T. However, the overall acquisition time was still too long for a broad application in the clinical setting. The aim of this study was to establish a shorter acquisition protocol whilst maintaining the contrast behavior and reproducibility.
CRIS-Team WoS Importer:2021-02-26